PRACTICE-ORIENTED CASES IN THE PROFESSIONAL TRAINING OF FUTURE CHEFS (Innovative professional education, 2024)
In the context of Ukraine's integration into the world educational space, the development of vocational education in the country should ensure the quality of professional training, which makes it important for vocational education institutions to focus on the ability of their graduates to practically implement the acquiredcompetencies. The use of practice-oriented cases helps to establish a close connection between theoretical knowledge and its practical implementation in the process of professional training of future chefs. Practice-oriented activities that model future production processes contribute to the productive development of theprofessional competence of future skilled workers.
Keywords: future chefs, professional training, professional competence, practice-oriented case, institution of vocational education and training